Pengaruh Literasi Keuangan Digital dan Self-Control Terhadap Penggunaan Paylater Pada Generasi Z di Kab. BONE - Yuli Rahma; Muhammad Fakhri Amir; Musrini Muis; Dhika Dzulkarnain Wibisono (Institut Agama Islam Negeri Bone, 2026)
This study aims to analyze the partial and simultaneous influence of Digital Financial Literacy and Self-Control on Paylater Usage among Generation Z in Bone Regency. The main problem of this study is to test the extent to which these two variabels influence paylater usage behavior. This quantitative research book the population of Generation Z paylater users in Bone Regency with a sampel of 100 respondents. The results of the study indicate that partially, Digital Financial Literacy has a significant effect on Paylater Usage, which is interpreted that literacy acts as a facilitator of overconfidence. Meanwhile, Self-Control has no significant effect,indicating that the fintech environment triggers instant gratification and reduces Self-Contro. However, simultaneously (F Test), X1 and X2 have a significant effect on Y. The implications of this study are input for regulator (OJK) to formulate more specific consumer education and protection policies regardian paylater risks, as well as increase Generation Z’s awareness of the importance of Self-Control to manage digital finances responsibly.